Reactive Power Minimization in Bidirectional DC-DC Converters Using a Unified-Phasor-Based Particle Swarm Optimization - Shi, Haochen; Wen, Huiqing; Hu, Yihua; Jiang, Lin (IEEE transactions on power electronics, 2018)
This paper deals with an optimized three-level modulated phase shift control using particle swarm optimization (PSO) strategy based on the unified phasor analysis with an aim to improve the efficiency of the bidirectional dual active bridge (DAB) converter for the whole operation range. A unified mathematical model based on Fourier transform is built for the DAB converter. All possible operation states under the three-level modulated phase shift control are covered. Accurate complex mathematical expressions for the inductor current, the transmission power, and the reactive power are obtained. Both modulus and angle variables are illustrated with respect to the inner and outer phase shift angle with the phasor diagram. The proposed method is able to achieve the minimum reactive power under three-level modulated phase shift control by obtaining the optimal phase-shift angles directly. The cumbersome process of the optimal operation mode selection for different voltage conversion ratio and load conditions in conventional methods is overcome successfully, thus greatly simplifying the theoretical calculation and implementation difficulty. Simulation and experimental results in terms of the reactive power, soft-switching range, and efficiency are provided to verify the practical feasibility of the proposed method for the bidirectional DAB converters.